The use of magnetic resonance and MR angiography in the detection of cerebral infarction: A complication of pediatric bacterial meningitis - Stošić-Opinćal Tatjana; Kačar Katarina; Stošić Srboljub; Lavrnić Slobodan; Perić Vesna; Gavrilov Mihail (Vojnosanitetski Pregled)
Bacground. Association of both cerebral infarction and acute bacterial meningitis is more common in younger patients than in the elderly. The rate of mortality and the frequency of sequel are very high inspite of the use of modern antibiotic therapy. In more than 30% of the cases of childhood bacterial meningitis, both arterial and venous infarctions can occur. The aim of this study was to present the role of the use of magnetic resonance (MRI), and MR angiography (MRA) in the detection of bacterial meningitis in children complicated with cerebral infarctions. Method. In the Centre for MR, the Clinical Centre of Serbia, 25 patients with the diagnosis of bacterial meningitis, of which 9 children with cerebral infarction whose clinical conditon deteriorated acutely, despite the antibiotic therapy, underwent MRI and MR angiography examination on a 1T scanner. Examination included the conventional spin-echo techniques with T1-weighted saggital and coronal, and T2- weighted axial and coronal images. Coronal fluid attenuated inversion recovery (FLAIR) and the postcontrast T1-weighted images in three orthogonal planes were also used. The use MR angiography was accomplished by the three-dimensional time-of-flight (3D TOF) technique. Results. The findings included: multiple hemorrhagic infarction in 4 patients, multiple infarctions in 3 patients, focal infarction in 1 patient and diffuse infarction (1 patient). Common sites of involvement were: the frontal lobes, temporal lobes and basal ganglia. The majority of infarctions were bilateral. In 3 of the patients empyema was found, and in 1 patient bitemporal abscess was detected. In 8 of the patients MR angiography confirmed inflammatory vasculitis. Conclusion. Infarction is the most common sequel of severe meningitis in children. Since the complication of cerebral infarction influences the prognosis of meningitis, repetitive MRI examinations are very significant for the evaluation of the time course of vascular involvement. The use of MRI, especially FLAIR imaging, confirmed its value in the detection and determination of the site and the extent of cerebral infarction. Non-invasive technique of examination, 3D TOF MR angiography clearly should show the presence of inflammatory vasculitis.